The Block Statue of Ḏd-ḥr - Metawi, Dina (Zeitschrift für ägyptische Sprache und Altertumskunde, 2019)
Publication of a block statue (JE 36668) with a separate fragmentary base (JE 36669). Both objects came from the Karnak Cachette and are on display in the Cairo Museum. The statue owner, a man named Ḏd-ḥr, held a number of important priestly titles, such as: jt-nṯr , ḥm-nṯr , ḥm-ḏw , and rdwy-nṯr of Amun at Karnak. The statue can be dated, on stylistic grounds, to the post-Persian Period.